2009
DOI: 10.1128/jvi.01139-08
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Simplex Virus Replication: Roles of Viral Proteins and Nucleoporins in Capsid-Nucleus Attachment

Abstract: Replication of herpes simplex virus type 1 (HSV-1) involves a step in which a parental capsid docks onto a host nuclear pore complex (NPC). The viral genome then translocates through the nuclear pore into the nucleoplasm, where it is transcribed and replicated to propagate infection. We investigated the roles of viral and cellular proteins in the process of capsid-nucleus attachment. Vero cells were preloaded with antibodies specific for proteins of interest and infected with HSV-1 containing a green fluoresce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
137
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(149 citation statements)
references
References 51 publications
5
137
1
Order By: Relevance
“…HSV-1 and adenovirus both directly bind to the cytoplasmic side of the NPC via nucleoporins (40,41,(68)(69)(70)(71). The adenoviral core protein protein VII has been shown to bind to several import proteins, including importin-␣, importin-␤, importin-7, and transportin, which are thought to mediate entry of the nucleoprotein through the NPC (39).…”
Section: Discussionmentioning
confidence: 99%
“…HSV-1 and adenovirus both directly bind to the cytoplasmic side of the NPC via nucleoporins (40,41,(68)(69)(70)(71). The adenoviral core protein protein VII has been shown to bind to several import proteins, including importin-␣, importin-␤, importin-7, and transportin, which are thought to mediate entry of the nucleoprotein through the NPC (39).…”
Section: Discussionmentioning
confidence: 99%
“…The transport receptor-cargo complex docks on NUPs, allowing passage across the NPC. Hepatitis B virus, herpes simplex virus, influenza virus, and adenovirus also use NUPs for nuclear entry (Trotman et al 2001;König et al 2008König et al , 2010Copeland et al 2009;Schmitz et al 2010), whereas poliovirus and cardiovirus induce modifications of NUPs (Gustin and Sarnow 2001;Porter and Palmenberg 2009). Previous LC-MS/MS studies revealed that KTN1, NUP43, NUP358, NUP45, and NUP54 expression is downregulated on HIV-1 infection while NUP358, NUP98, and TPR expression is upregulated (Chan et al 2007; Monette et al 2011).…”
Section: Nucleoporins (Nups)mentioning
confidence: 99%
“…In summary, RANBP2 aids nuclear import by at least two mechanisms: i) by "capturing" transport receptors through the FG-repeats, it conveys them towards the NPC and reduces the effective concentration of import receptors required for efficient transport, while ii) by interacting with selected cargos in a receptor-independent manner, through the RANBP2 N-ter domain, it increases the overall efficiency of nuclear import. Interestingly, RANBP2 is also implicated in the nuclear delivery and integration of certain human viruses, including Herpes simplex (Copeland et al, 2009) and immunodeficiency virus-1 (HIV-1) (Zhang et al, 2010;Ocwieja et al, 2011;). …”
Section: Ranbp2 In Interphase Nucleocytoplasmic Transportmentioning
confidence: 99%